2018
DOI: 10.1371/journal.pntd.0006197
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni infection suppresses the growth of Plasmodium yoelii parasites in the liver and reduces gametocyte infectivity to mosquitoes

Abstract: Malaria and schistosomiasis are major parasitic diseases causing morbidity and mortality in the tropics. Epidemiological surveys have revealed coinfection rates of up to 30% among children in Sub-Saharan Africa. To investigate the impact of coinfection of these two parasites on disease epidemiology and pathology, we carried out coinfection studies using Plasmodium yoelii and Schistosoma mansoni in mice. Malaria parasite growth in the liver following sporozoite inoculation is significantly inhibited in mice inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Schistosomiasis affects almost 210 million people worldwide, and an estimated 200,000 people die from it each year. Co-infection of malaria and schistosomiasis in the tropics is common (Keiser and Utzinger 2012;Moriyasu et al, 2018). With increasing migration and travel between infested areas of the world, bilharzia is even becoming a threat to more developed regions like Europe, mainly because doctors are not trained in diagnosing and treating the NTDs that are more common in the developing world (de Laval et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Schistosomiasis affects almost 210 million people worldwide, and an estimated 200,000 people die from it each year. Co-infection of malaria and schistosomiasis in the tropics is common (Keiser and Utzinger 2012;Moriyasu et al, 2018). With increasing migration and travel between infested areas of the world, bilharzia is even becoming a threat to more developed regions like Europe, mainly because doctors are not trained in diagnosing and treating the NTDs that are more common in the developing world (de Laval et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the peak of malaria parasitaemia was decreased in mice co-infected P. yoelii , but not in those co-infected with P. chabaudi ( 7 ). Conversely, the growth of P. yoelii in the liver was inhibited in mice co-infected with S. mansoni , and malaria parasite gametocyte infectivity was much reduced ( 14 ).…”
Section: Malariamentioning
confidence: 99%
“…In human populations, some studies have been conducted to generate an in-depth understanding of the interaction between concomitant infections with malaria parasites and Schistosoma , but these studies showed contradictory results. Some studies suggested a protective role for helminths [1821, 4750]; for example, one cross-sectional study demonstrated lower P. falciparum parasite densities in children with mild S. haematobium infection than those in the control group [18, 19], and a further study suggested an age-dependent manner of the protective effect [47]. Animal experiments also reported similar results where parasite growth and gametocyte infectivity of Plasmodium yoelii or Plasmodium knowlesi were both inhibited by coinfection with Schistosoma mansoni [20, 21] .…”
Section: Main Textmentioning
confidence: 99%